OP0167 A randomized, double-blind, phase 1 study demonstrates equivalence in pharmacokinetics, safety, and efficacy of CT-P13 and infliximab in patients with ankylosing spondylitis. (23rd January 2014) - Park, W.; Hrycaj, P.; Kovalenko, V.; Miranda, P.; Gutierrez-Ureña, S.; Lee, Y.; Lim, M.; Ahn, C.; Kim, H.; Yoo, D.; Braun, J.
Abstract : Background: CT-P13 was developed as a biosimilar product to infliximab (Remicade®), a chimeric monoclonal antibody approved in the European Union in 1999 for the treatment of rheumatoid arthritis (RA), ankylosing spondylitis (AS), Crohn's disease, ulcerative colitis, psoriasis, and psoriatic arthritis. Objectives: To compare the pharmacokinetic (PK) profile of CT-P13 with that of infliximab at steady state in terms of area under the concentration-time curve over a dosing interval (AUCτ ) and observed maximum serum concentration (Cmax, ss ), and evaluate the efficacy and overall safety of both treatments in patients with AS. Methods: Two hundred fifty patients with active AS were randomized 1:1 to receive either CT-P13 or infliximab (5 mg/kg, 2-hour IV infusion per dose) at weeks 0, 2, and 6 (dose-loading phase) and at weeks 14, 22, and 30 (maintenance phase). Ratios of geometric means of primary PK parameters (AUCτ and Cmax, ss ) from the 2 treatment arms between weeks 22 and 30 were subjected to ANCOVA analysis at 90% confidence intervals (CIs). Efficacy measures (including ASAS20 and ASAS40), and safety parameters (including the incidence of adverse events [AEs]) were also evaluated. This report presents PK, efficacy, and safety results up to week 30 (as approved by the European Medicines Agency). Results: The mean (% CV) AUCτ was 34855.45 (34.3%) μg-h/mL and 34688.71 (45.4%) μg-h/mL in the CT-P13 and infliximab arms, respectively. The mean (% CV) Cmax, ss was 153.52 (27.6%) μg/mL and 150.39 (26.9%) μg/mL in the CT-P13 and infliximab arms, respectively. The ratio (%) between the geometric means of the AUCτ and Cmax, ss values in the CT-P13 and infliximab arms were 104.1% (90% CI 93.9% to 115.4%) and 101.5% (90% CI 94.6% to 108.9%), respectively, between weeks 22 and 30, indicating PK equivalence in terms of AUCτ and Cmax, ss . Secondary parameters at week 30 were also comparable, including ASAS20 and ASAS40 response rates (70.5% for CT-P13 vs 72.4% for infliximab and 51.8% vs 47.4%, respectively). AEs considered by the investigators to be related to study treatment were reported in 57 (44.5%) patients and 58 (47.5%) patients in the CT-P13 and infliximab arms, respectively. Related AEs due to infection were reported for 24/128 (18.8%) patients and 22/122 (18.0%) patients in the CT-P13 and infliximab treatment groups, respectively. AEs due to infusion reactions considered related to study drug were reported in 5 patients in the CT-P13 arm, and 6 patients in the infliximab arm. Tuberculosis was reported in 2 patients in the CT-P13 arm and in 1 patient in the infliximab arm. Conclusions: CT-P13 and infliximab are equivalent in terms of AUCτ and Cmax, ss in patients with AS. In addition, CT-P13 was well tolerated, with an efficacy and safety profile comparable to that of infliximab up to week 30. Disclosure of Interest: W. Park: None Declared, P. Hrycaj: None Declared, V. Kovalenko: None Declared, P. Miranda: None Declared, S. Gutierrez-Ureña: None Declared, Y. Lee: None Declared, M. Lim: None Declared, C. Ahn: None Declared, H. Kim Employee of: Celltrion, D. Yoo: None Declared, J. Braun: None Declared